Quantitative assessment of xanthelasma palpebrarum treated by argon laser photocoagulation using ImageJ software - Moustafa A Salamah; Tamer G Elsayed (Delta Journal of Ophthalmology, 2022)
Purpose The aim of this study was to evaluate the effect of argon laser photocoagulation on xanthelasma using ImageJ software. Patients and methods The study included 41 eyes of 23 patients (49 individual xanthelasmic lesions). All lesions were treated by a single session of argon laser photocoagulation. The lesions were assessed prelaser and postlaser using ImageJ software. Results All xanthelasmic lesions improved in height and color. The pretreatment mean height in ImageJ was 168.93±11.64 pixels, while the mean posttreatment height was 131±8.39 pixels (P<0.001). The color moderately improved in 24.4% of the cases and markedly improved in 68.3% of the cases. Conclusion Argon laser treatment of xanthelasma is a safe and effective treatment modality. This finding was documented using ImageJ software.